2021
DOI: 10.3390/ijms222111387
|View full text |Cite|
|
Sign up to set email alerts
|

The Dynamism of Transposon Methylation for Plant Development and Stress Adaptation

Abstract: Plant development processes are regulated by epigenetic alterations that shape nuclear structure, gene expression, and phenotypic plasticity; these alterations can provide the plant with protection from environmental stresses. During plant growth and development, these processes play a significant role in regulating gene expression to remodel chromatin structure. These epigenetic alterations are mainly regulated by transposable elements (TEs) whose abundance in plant genomes results in their interaction with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 355 publications
(303 reference statements)
0
34
0
2
Order By: Relevance
“…In plants and animals, different forms of stress are known to act as triggers or facilitators of TE mobility [140,141]. Several studies in plants have reported overexpression of TEs following abiotic or biotic stress conditions such as temperature, nitrate de-privation, and wounding [142][143][144][145]. Activation of TEs in response to different stresses has also been demonstrated in insects [146], and especially in the context of insecticide resistance [147][148][149].…”
Section: Role Of Stress and Environmental Pollution In Te Mobility An...mentioning
confidence: 99%
“…In plants and animals, different forms of stress are known to act as triggers or facilitators of TE mobility [140,141]. Several studies in plants have reported overexpression of TEs following abiotic or biotic stress conditions such as temperature, nitrate de-privation, and wounding [142][143][144][145]. Activation of TEs in response to different stresses has also been demonstrated in insects [146], and especially in the context of insecticide resistance [147][148][149].…”
Section: Role Of Stress and Environmental Pollution In Te Mobility An...mentioning
confidence: 99%
“…As the genome of Saccharina latissima remains unpublished as of now, we mapped the high-quality reads to the genome of the closely related species Saccharina japonica (Fan et al, 2020;v6.2 from ORCAE (Sterck et al, 2012)). The 476,161,873 trimmed reads (All TrimmedReads, Table S1) were mapped with the SOAP aligner (v1.11, Li et al, 2008) to 548,536,073 in silico digested MethylRAD tags (1,793,114 with CCGG recognition sites,527,987 CCTGG,496,183 CCTGT and 527,729 CCAGG) that we had extracted from the S. japonica genome with a custom python script InSilicoTypeIIbDigestion_corrected.py (https://gist.github.com/alj19 83/a1bcb950013d8ffac9a7fb9ceb70b1c0). For mapping, we used the following specifications: two mismatches allowed (-v 2), sanger quality +33 (-z!…”
Section: In Silico Digestionmentioning
confidence: 99%
“…Several studies have suggested that TEs are involved in critical physiological functions such as regulation of stem cell properties, epithelial to mesenchymal transition, inflammation, and many more biological functions [ 40 ]. Evidence also suggests that TEs in mammals have contributed to adaptive characteristics such as increased gene expression, gene replication, and stress tolerance [ 68 ]. Of note, some of the most important physiological contributions are from the TE-derived genes, which in turn participate in a variety of biological functions [ 40 ].…”
Section: Physiological Functions Of Tes In the Host Cellsmentioning
confidence: 99%